2012
DOI: 10.1097/naq.0b013e318258c4e0
|View full text |Cite
|
Sign up to set email alerts
|

Use of Video-Feedback, Reflection, and Interactive Analysis to Improve Nurse Leadership Practices

Jeannette T. Crenshaw

Abstract: The chronic shortage of registered nurses (RNs) affects patient safety and health care quality. Many factors affect the RN shortage in the workforce, including negative work environments, exacerbated by ineffective leadership approaches. Improvements in the use of relationship-based leadership approaches lead to healthier work environments that foster RN satisfaction and reduce RN turnover and vacancy rates in acute care settings. In this article, an innovative approach to reduce nurse turnover and decrease va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…10,12,[15][16][17][18] The use of VF originated in athletics learning, 19 which inspired robust literature supporting VF as an effective means of improving communication skills in healthcare education. 11,12,15,[20][21][22][23] When applied to medical procedural skills, there are fewer studies that investigate its effectiveness as a procedural teaching tool. The Kirkpatrick model is a well-established educational model used to rank the impact of educational programs.…”
Section: Résumémentioning
confidence: 99%
“…10,12,[15][16][17][18] The use of VF originated in athletics learning, 19 which inspired robust literature supporting VF as an effective means of improving communication skills in healthcare education. 11,12,15,[20][21][22][23] When applied to medical procedural skills, there are fewer studies that investigate its effectiveness as a procedural teaching tool. The Kirkpatrick model is a well-established educational model used to rank the impact of educational programs.…”
Section: Résumémentioning
confidence: 99%
“…In occupational health, video has been used to assess and evaluate posture and movements during work (Hakkarainen, Ketola, & Nevala, 2011 ; Soares et al, 2012 ). Within healthcare education and professional development, video feedback has shown to be beneficial in supporting postliminary reflection on in-action activities in group meetings (Carroll, Iedema, & Kerridge, 2008 ; Crenshaw, 2012 ; Iedema et al, 2009 ). Video feedback has also been considered to be useful in clinical skills training in nursing education as a basis for reflection about a training activity (Johannesson, Silén, Kvist, & Hult, 2013 ).…”
mentioning
confidence: 99%
“…Furthermore, some previous studies have clarified how supervisors or peers should provide feedback. Video feedback with reflection and interactive analysis is an untapped resource for nurse leaders and aspiring nurse leaders in their development of effective leadership skills [7]. Participants using peer-to-peer shadowing as a technique for the development of mid-level nurse managers in clinical leadership found that balancing the act of stepping in and taking action or just observing and giving or withholding feedback are important practices that are difficult to develop [8].…”
Section: Introductionmentioning
confidence: 99%